Novel Anti-cancer Agents and Cellular Targets and Their Mechanism(s) of Action - Allison, Simon J (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Patient outcomes remain poor for many cancers despite improvements in treatments and new molecular-targeted biomedicines for certain cancer types or subtypes. Dose-limiting toxicity, a narrow therapeutic index, and the development of resistance to traditional anti-cancer agents are well-established. It is apparent that inherent and acquired drug resistance are major challenges with molecular-targeted agents and that on- as well as off-target side effects can still occur. Other issues include drug metabolism by the body and safely supplying a sufficient amount of active drug to the tumor cells. There is a clear and urgent need for new molecular targets and drugs that specifically target cancer cells in different ways to existing approved drugs. This book, through a collection of eight research articles and two review articles from the Biomedicines themed Special Issue 'Novel Anti-Cancer Agents and Cellular Targets and Their Mechanism(s) of Action', provides a snapshot of some of the diverse and exciting research approaches being taken by the cancer research community in trying to address some of these therapeutic challenges.